THE IMPLEMENTATION OF GOOGLE CLASSROOM TO TEACH READING NARRATIVE TEXT - Guntur Esa Mukti; Etika Rachmawati; Wawan Tarwana (Universitas Galuh, 2021)
This paper reports the investigation of Google Classroom (GC) implementation to teach reading of narrative text to students of Vocational High School. It was purposed to find out teacher’s strategy to implement GC to teach reading of the narrative text, students’ perception to the implementation of GC teaching reading of the narrative text, and teacher’s perception of the implementation of GC to teach reading of the narrative text. This study used qualitative research under case study approach to take data from participants. In this case, the participants were the tenth grade and an English teacher. Furthermore, observations, questionnaires, and interviews were media to collect the data. The results showed that the teacher used Google Classroom as a medium to share assignments and learning material that should be studied by the students. During the learning process was occurred, the teacher and students only need to open the learning material in their smartphone and discussed it together through questioning activities. Then, related to how the teacher taught reading to his students, the teacher applied several reading techniques. Furthermore, most of the students gave quite positive responses to Google Classroom. They agreed that by implementing Google Classroom as a learning medium, learning activities became more structured and enjoyable. Then, the teacher perceived this application helpful. He mentioned that this application made him easy to manage his class.Keywords: MALL, Google Classroom. Reading, Narrative text.